The Effects of Being Subject to the Colombian Apprenticeship Contract on Manufacturing Firm Performance - Ospino, Carlos (2018)
This paper evaluates the intent to treat local average treatment effects of the Colombian apprenticeship contract on manufacturing firm dynamics taking advantage of an exogenous variation generated by the 2002 labor reform and the regulation design. This evaluation is appealing because very little is known about the effects of apprenticeship policies on firm dynamics in developing countries. Moreover, although this regulation has been in place for years it has not been evaluated. Results using a regression discontinuity design which compares small firms subject to the regulation to those that are not, shows positive effects on output per worker (10 log points), total factor productivity (3 log points) and the share of exported sales (2 percentage points). It also shows a negative effect on the average wage bill of directly hired workers (9 log points). These results suggest that small firms which became subject to the regulation adjusted their labor force more efficiently, thus increasing productivity but did not share these gains with workers through higher wages.